Pengaruh Diskon Dan Gratis Ongkos Kirim Terhadap Keputusan Pembelian Pada Marketplace Shopee Di Desa Batunagodang Siatas Kabupaten Humbang Hasundutan - Aprilidia Rojelita Siringoringo; Natalia E.T. Sihombing; Kepler Sinaga (Research and Community Service UNIVERSITAS KALBIS, 2026)
This study aims to analyze the effect of Discount (X_1) and Free Shipping (X_2) on Purchasing Decisions (Y) on the Shopee marketplace in Batunagodang Siatas Village, Humbang Hasundutan Regency, both partially and simultaneously. The research method used is a quantitative approach with a sample of 87 respondents. Data were collected through questionnaires, including primary and secondary data, which were then tested using validity, reliability, and classical assumption tests. Data analysis was carried out using multiple linear regression which produced the equation Y = 5.945 + 0.230X_1 + 0.649X_2. The results of hypothesis testing through the t-test showed that the Discount variable had a significant and positive effect on purchasing decisions (t_count 4.577 > t_table 1.989). The Free Shipping variable also showed a significant and positive effect with a t_count value of 6.334 > t_table 1.989. Overall, the coefficient of determination (R Square) of 0.363 indicates that the independent variables contribute 36.3% to purchasing decisions. Meanwhile, the remaining 63.7% is influenced by other variables not examined in this study, such as price, product quality, promotion, consumer trust, and service quality.